Rancang Bangun Sistem Informasi E-Voting Untuk Pemilihan Ketua OSIS Menggunakan Metode Prototype Berbasis Web - Chairul Rizal; Jelita Purwanti; Poppy Nabilla; Cindy Hartika; Latipah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The election of the OSIS Chair at the high school and vocational school level is still conventional, so it requires a lot of funds to be spent. Apart from that, many students were unable to vote because they were unable to attend due to illness or other reasons. Along with the development of sophisticated technology in this modern era, researchers want to implement Android-based general elections or what is called e-voting. This research aims to design an Android-based e-voting application and test the feasibility of the e-voting application product in the election of OSIS chairman and deputy chairman. Quantitative type research methods using the Research and Development (RnD) model with data testing tools using SPSS 16.0 for Windows as well as developing e-voting applications using prototype methods can make voting easier, reduce data manipulation, reduce voting twice and also speed up calculations and reporting. Based on the results of black box testing on the e-voting system, the trial was successful, so it can be implemented in the process of selecting the Chair and Deputy Chair of the OSIS in SMA/SMK. Feasibility trials carried out by 7 voters/users. The feasibility level for the Android-based e-voting system was 84.17%, which means it is very feasible.